Administration of AS03B-adjuvanted A(H1N1)pdm09 vaccine in children aged <3 years enhances antibody response to H3 and B viruses following a single dose of trivalent vaccine one year later. - Hoschler, K; Andrews, N; Faust, SN; Finn, A; Pollard, A; Snape, M; Walker, W; Zambon, M; Miller, E (2014)
BACKGROUND: We report on a follow-up clinical and serological investigation of 274 children who received seasonal influenza vaccine (trivalent inactivated vaccine [TIV]) 1 year after receipt of either AS03(B)-adjuvanted subunit or whole virus monovalent A(H1N1)pdm09 vaccine and describe the antibody responses to the H3N2 A/Perth/16/2009 and B/Brisbane/60/2008 components of TIV. METHODS: Vaccine responses were analyzed using hemagglutination inhibition (HAI) assays. In children aged <3 years, previous receipt of adjuvanted vaccine resulted in higher HAI antibody responses to H3N2 and B strains compared with nonadjuvanted vaccine (fold change 16.8 vs 4.3 for H3N2 and 7.0 vs 1.6 for B). In children aged >3 years, responses to the H3 and B components of TIV were similar between vaccine groups. Sera taken before and after the pandemic vaccine were also analyzed by HAI using A/Perth/16/2009 virus. This analysis showed that 11.1% of children receiving the AS03(B)-adjuvanted vaccine but only 1.4% in the nonadjuvanted group had a 4-fold rise to A/Perth/16/2009. CONCLUSION: AS03B-adjuvanted A(H1N1)pdm09 influenza vaccine generates a cross-reactive antibody response to H3N2 in children and enhances responses to heterologous subtypes in children aged <3 years 1 year later.